Development of an advertisement tax system based on a geographic information system - Alkan, Mehmet; Surmeneli, Hicret Gursoy (ICE PUBLISHING, 2018)
In recent years, rapid urbanisation has resulted in an accelerated increase in production and consumption. A major contribution to the transformation from production to consumption is made by the marketing and advertising sectors. The advertising method most connected with urbanisation is outdoor advertising, which involves publicising products through media such as billboards, posters, screens, totems and zeppelin. The design and implementation of outdoor advertising should be aesthetically, environmentally and culturally aware to preserve the historical and cultural particularities of urban areas and to prevent pollution. In addition, there is a trade dimension to the advertising work being undertaken. The income from rental of advertising space is liable to tax under the law. The prepaid taxes are given back to the municipalities through public services. This study aimed to bring a different perspective to storing advertisement data and monitoring advertisement tax. For this purpose, a positional database based on a geographic information system was created using the advertisement and tax data from a district of Istanbul, Turkey. All parameters were found to respond to positional queries and were visualised on a map.
Keywords: economics & finance; information technology; municipal & public service engineering; URBAN; DISTRACTION; DESIGN; Engineering